Chemical looping steam reforming of methane over Ce-doped perovskites. (21st September 2020) - Zhang, Xianhua; Su, Yinghui; Pei, Chunlei; Zhao, Zhi-Jian; Liu, Rui; Gong, Jinlong
Graphical abstract: Highlights: La1- x Ce x FeO3 (x = 0, 0.5, 1) catalysts with orthorhombic structure were designed and prepared. A site Ce 3+ substitution improved the surface reactivity in H2 O splitting step. La0.5 Ce0.5 FeO3 exhibited high oxygen restoration kinetics in re-oxidation step. A redox mechanism for La0.5 Ce0.5 FeO3 in chemical looping was proposed. Abstract: Chemical looping steam reforming of methane (CL-SRM) has emerged as an attractive pathway on H2 O splitting for H2 production. However, this process still faces a major challenge in efficiently producing H2 with high redox kinetics and yields. In this paper, the promoting effects of Ce 3+ substitution into LaFeO3 redox catalysts on thermochemical H2 O splitting as well as partial oxidation of methane are presented. An appropriate amount of Ce 3+ substitution in A site of LaFeO3 (La0.5 Ce0.5 FeO3 ) promotes the lattice oxygen conversion rate in methane partial oxidation step and boosts the reaction kinetics in H2 O splitting step by enhancing the surface water activation and lattice oxygen mobility of the perovskite. In the CL-SRM process, the perovskite is reduced into Fe 0 /(La0.5 Ce0.5 )2 O3 and Fe 0 /(La0.5 Ce0.5 )O2- x phases in methane partial oxidation step and recovered to the original perovskite structure in H2 O splitting step with simultaneous production of hydrogen, which maintains a reversible phase transformation during 100 redox cycles. As a result, the La0.5 Ce0.5 FeO3 achieves high stability with the superior performance for syngas and hydrogen production. These findings provide the fundamental understanding on the synergy between the catalytic sites and enhanced lattice oxygen mobility for the promotion of H2 O activation and hydrogen productivity in chemical looping process.